IMPROVING MOBILITY IN KEDIRI CITY WITH MKJI ANALYSIS 1997 AND TIME SLICE AT SIMPANG EMPAT DHOHO PLAZA - Hidiyati, Evita Fitrianis; Nugroho, Laksono Djoko; Haris Muhammadun (International Journal Science and Technology, 2023)
The city of Kediri, as the third largest city in East Java, has cultural heritage, history and natural beauty that attracts visitors from various regions. However, population growth and motorized vehicles cause traffic jams. Signalized intersections, which are a solution to control intersection conflicts, require knowledge of intersection saturation flows to plan efficient traffic management. Analysis methods such as MKJI 1997 and Time Slice with Vehicle Operating Cost (BOK) calculations help design effective solutions. This research shows that adjusting cycle times, increasing effective width, and optimizing signals can improve transportation system performance and reduce congestion in Kediri City. Cycle time analysis taking into account factors such as vehicle type, traffic volume, and vehicle speed resulted in a cycle time of 90.7 seconds. The impact can be seen in the Degree of Saturation (DS) at various intersection arms, with service variations from E to F. Research also shows a decrease in waiting time/queuing for signal lights from 135 seconds to 118 seconds, which results in a decrease in the degree of saturation (DS) and changes in time cycle. The use of Smart Traffic Lights and traffic engineering, such as immediate left turns on the east arm and additional signs, is required. Evaluation of congestion cost efficiency shows that changing the value of side barriers can save Rp. 22,679,183 in the next five years.